Applied Micromechanics of Porous Materials - Dormieux, Luc; Ulm, Franz-Josef (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2005)
Poromechanics is the mechanics of porous materials and is now a well established field in many engineering disciplines, ranging from Civil Engineering, Geophysics, Petroleum Engineering to Bioengineering. However, a rigorous approach that links the physics of the phenomena at stake in porous materials and the macroscopic behaviour is still missing. This book presents such an approach by means of homogenization techniques. Rigorously founded in various theories of micromechanics, these up scaling techniques are developed for the homogenization of transport properties, stiffness and strength properties of porous materials. The special feature of this book is the balance between theory and application, providing the reader with a comprehensive introduction to state-of-the-art homogenization theories and applications to a large range of real life porous materials: concrete, rocks, shales, bones, etc.